2021
DOI: 10.3389/fphys.2021.723454
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Associated With Light Perception and Physiological Responses of Birds

Abstract: Environmental light that animal receives (i.e., photoperiod and light intensity) has recently been shown that it affects avian central nervous system for the physiological responses to the environment by up or downregulation of dopamine and serotonin activities, and this, in turn, affects the reproductive function and stress-related behavior of birds. In this study, the author speculated on the intriguing possibility that one of the proposed avian deep-brain photoreceptors (DBPs), i.e., melanopsin (Opn4), may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 93 publications
(135 reference statements)
0
3
0
Order By: Relevance
“…For the first time, the avian VTA was suggested as an important area of the midbrain of birds involved in the light perception by melanopsin (Opn4, photoreceptor) and might be involved in the welfare of poultry (Kang, 2021). To evaluate the long-term effects of light intensity programs on the previously identified melanopsin (photoreceptor), the expression of Opn4 gene was determined at 14 and 42 days of age (Figure 8).…”
Section: Regulation Of Welfare Marker and Melanopsin Genes In The Ven...mentioning
confidence: 99%
See 1 more Smart Citation
“…For the first time, the avian VTA was suggested as an important area of the midbrain of birds involved in the light perception by melanopsin (Opn4, photoreceptor) and might be involved in the welfare of poultry (Kang, 2021). To evaluate the long-term effects of light intensity programs on the previously identified melanopsin (photoreceptor), the expression of Opn4 gene was determined at 14 and 42 days of age (Figure 8).…”
Section: Regulation Of Welfare Marker and Melanopsin Genes In The Ven...mentioning
confidence: 99%
“…Many studies provide evidence that light can affect the central physiology of animals independent of the retinal function (Underwood et al, 1984;Wade et al, 1988;Fernandes et al, 2013). VTA was suggested as an important area of the midbrain involved in the light perception by melanopsin (Opn4, photoreceptor) and might be involved in the avian welfare (Kang, 2021). The result of long-term effects of light intensity programs on Opn4 expression at 42 days of age in the present study suggests that Opn4 in VTA may be involved in the direct perception of light intensity information for physiological adaptation of birds.…”
Section: Regulation Of Welfare-indicating Genes and Melanopsin (Opn4)...mentioning
confidence: 99%
“…In the evolutionary plan, significant changes have occurred, particularly in the structure of integrating organs. In birds, the nervous system reaches a significantly high degree of development and differentiation (Kang, 2021). Representatives of the bird class have several biological features: the development of the embryo outside the mother's body, physiological precociousness, rapid growth, high body temperature (+40-42 °С), the peculiarity of the structure of the skin and its derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…VTA-GR is well known for regulating the stress and reward system regulating feeding behavior [22,23]. In recent studies of broiler chickens, avian VTA was suggested as the important region, consisting of a variety of neurons of the avian midbrain, that is involved in light perception by Opn4 (melanopsin) and might be involved in broilers' welfare [10,24].…”
Section: Introductionmentioning
confidence: 99%